Manajemen Pendukung Pengambilan Keputusan Pelayanan Dalam Upaya Aspek Promotif, Preventif Dan Kuratif Masalah Kesehatan Kulit Berbasis Evidence Based Practice - Nazara, Desman Serius; Arda, Darmi; Nawangwulan, Kurniati; Asrianto, Asrianto; Wahyudianti, Ni Luh Gede Sri; Fitriani.K, Fitriani.K; Mustarin, Yanti; Riswan, Riswan (Asosiasi Guru dan Dosen Seluruh Indonesia, 2025)
Scabies is an epidemic disease in many communities. This disease is often found in children and young adults, but can also affect all ages. The incidence is the same in men and women. The purpose of the study was to improve the knowledge and skills of all residents of the orphanage in the promotive, preventive, and curative aspects of skin diseases. The research method used was Decision Making Services in Efforts for Promotive, Preventive and Curative Aspects of Skin Health Problems Based on Evidence Based Practice. The results of the study showed that personal hygiene had a significant relationship with the incidence of scabies at the Tamalanrea Makassar Orphanage. The conclusion of the study showed that there was a significant relationship between personal hygiene and the incidence of scabies. We hope that physical skin examination activities at the Tamalanrea Makassar Orphanage are always carried out to avoid scabies.